Mewartakan Kebenaran Kepada Generasi Z: Aktualisasi Iman dalam Praktik Sosial dan Relasional berdasarkan Yakobus 2:18 - Firman Panjaitan; Syenitesalonika H.C. Boimau (Teokristi: Jurnal Teologi Kontekstual dan Pelayanan Kristiani, 2026)
Preaching faith in the digital age faces new challenges, especially in reaching out to Generation Z who live amid a culture of pluralism, moral relativism, and digital connectedness. This study aims to examine the theological meaning of James 2:18 in the context of preaching the Christian faith to a Gen Z group that is known for its digital, plural characteristics, and search for authentic spirituality. Using qualitative methods based on literature review and a historical-critical approach, this study interprets the Greek text grammatically and contextually to highlight the relationship between faith and deeds. The results showed that faith that is not realized in concrete actions does not have Effective Preaching power for Gen Z in contrast to previous studies that emphasized digital strategies or message delivery, this study focused on the integration of faith and action as authentic forms of preaching. This study concludes that the proclamation of faith should be voiced through real-life evidence and relational, not just through words or digital media alone. The main contribution of the study is a new theological framework that underlines the importance of the actualization of faith and social practice as contextual and transformative preaching for today's generation. Keywords: Generation Z; Faith and Works; James 2:18; Preaching